Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Pemecahan Masalah dan Berpikir Kritis Peserta Didik - Rosiatul Ismi; Ni Nyoman Sri Putu Verawati; I Wayan Gunada (Kappa Journal, 2022)
This study aims to determine whether there is an effect of the problem-based learning model on the problem-solving and critical thinking skills of class XI students of SMAN 1 Praya Tengah. experimental and control classes, where class XI IPA 2 is the experimental class and class XI is IPA 3 is the control class. The experimental class was given treatment in the form of applying a problem-based learning model and the control class was given treatment in the form of applying a direct instruction learning model. Data on problem-solving abilities and critical thinking were measured using a comparison of the initial test with the final test in the form of 8 essay questions to measure problem solving abilities and 4 essay questions. to measure students' critical thinking skills. The research hypotheses were tested with the manova test with a significant level of 5%. Based on the results of the analysis that has been carried out, the results of the hypothesis that Ho is rejected and H is accepted. So it can be concluded that there is an effect of problem-based learning model in improving problem solving and critical thinking